The Effect of Variation of Binding Materials on The Physical Quality of Batik Clam Shell Extract Tablets (Paphia undulata B.) - Rifka Nabila (Strada Journal of Pharmacy, 2021)
Indonesia is the largest archipelagic country which has shell commodities reaching around 2.752 tons with calcium content which can be utilized for the growth and development of the human body. One type of shellfish that is often found is batik clam (Paphia undulata B.). In order to utilize the shells of batik shells, research was carried out by determining the formulation and knowing the effect of variations in the type of binder on the physical quality of the preparation of batik shell extract tablets. Tablets were prepared by wet granulation method using three different binders namely FI (PVP), FII (gelatin), and FIII (CMC-Na) with a concentration of 4%. The data obtained were analyzed using the one way ANOVA test. The results showed that the various types of binder materials had a different effect on the physical quality of the tablets produced, based on the results of the ANOVA test analysis which showed a significant value of 0.000 (p <0.05). Formulations that have good physical tablet quality namely FI with PVP binder and FII with gelatin binder, with a hardness test value of 14.44 kg ± 1.24; 12.57 ± 0.74 and a friability test of 0.20% ± 0.07; 0.38% ± 0.08 which is almost close to K+ (calcium lactate) of 17.47 kg ± 0.54 and 0.21% ± 0.05.